Bifunctional Therapy by Zinc‐Cobalt Bimetal‐Organic Framework with Encapsulated Doxorubicin to Overcome Drug‐Resistance. Issue 12 (14th October 2019) - Wang, Licheng; Hou, Hanyi; Jiao, Xinqi; Shen, Tianyin; Liu, Yingying; Qiao, Yida; Liu, Yu; Lu, Yuan; Ge, Jun
Abstract: Drug resistance is a major challenge in antineoplastic chemotherapy, which could be possibly solved through multifunctional anti‐cancer therapy. This study constructs a drug delivery system with Zn(II)‐Co(II) bimetal‐organic framework nanoparticles with encapsulated doxorubicin (DOX), a model chemotherapeutic molecule. Beyond conventional therapeutic mechanisms powered by DOX, the newly applied Co(II) to the drug delivery system catalyzes the generation of reactive oxygen species (ROS) through a Fenton‐like process, leading to necrosis due to oxidative stress beyond threshold. The system displayed DOX‐based and Co(II)‐based dual mechanism anti‐cancer therapy to overcome DOX‐resistance while demonstrating significant cytotoxicity promotion in non‐resistant cell lines, as effects of ROS were further acknowledged by following cell characteristic examinations. This bifunctional DOX‐encapsulated bimetal‐organic framework nanoparticle opens a new strategy to construct multiple anti‐cancer mechanism drug delivery systems with great simplicity. Abstract : Irresistible : An antineoplastic chemotherapeutic nanoparticle (NP) is constructed based on zinc‐cobalt bimetal‐organic frameworks encapsulated with doxorubicin (DOX). Therapeutic effects are tested on cancer cell lines and its DOX‐resistant counterparts, and cellular characteristics are further examined to demonstrate the effectiveness of NPs in overcoming drug‐resistance.